2021
DOI: 10.3389/fimmu.2021.660230
|View full text |Cite
|
Sign up to set email alerts
|

Early Initiation of Tocilizumab Treatment Against Moderate-to-Severe Myelitis in Neuromyelitis Optica Spectrum Disorder

Abstract: BackgroundInterleukin-6 receptor blockade is effective in reducing the risk of relapses in neuromyelitis optica spectrum disorder (NMOSD). However, its efficacy during acute attacks of NMOSD remains elusive.ObjectiveWe investigated the effects of tocilizumab on disability during acute attacks, as well as its maintenance, in patients with moderate-to-severe myelitis.MethodsNineteen patients with NMOSD received tocilizumab treatment as add-on to high-dose methylprednisolone (HDMP) in acute myelitis and twenty-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Our findings agree with other retrospective studies that found an increased concentration of CSF IL-6 in NMOSD (17,28,29) and MOGAD (17,30) compared to MS. Added to our results, these findings suggest that CSF IL-6 measurement may impact early diagnosis, while cytokine measurement is easy and fast to perform as compared to aquaporin-4 or MOG antibody, and may guide early therapeutic action, in suspected NMOSD/ MOGAD patients. Moreover, tocilizumab, an IL-6 receptor blockade therapy, has shown promising efficacy in NMOSD (31)(32)(33) and has been reported to be effective in relapsing steroid-dependent MOGAD (31,34), reinforcing the impact of the IL-6 pathway in these diseases. In contrast, CSF CD25 could not separate MSARD from NMOSD and MOGAD, as it has already been suggested in two previously published retrospective studies (17,35).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings agree with other retrospective studies that found an increased concentration of CSF IL-6 in NMOSD (17,28,29) and MOGAD (17,30) compared to MS. Added to our results, these findings suggest that CSF IL-6 measurement may impact early diagnosis, while cytokine measurement is easy and fast to perform as compared to aquaporin-4 or MOG antibody, and may guide early therapeutic action, in suspected NMOSD/ MOGAD patients. Moreover, tocilizumab, an IL-6 receptor blockade therapy, has shown promising efficacy in NMOSD (31)(32)(33) and has been reported to be effective in relapsing steroid-dependent MOGAD (31,34), reinforcing the impact of the IL-6 pathway in these diseases. In contrast, CSF CD25 could not separate MSARD from NMOSD and MOGAD, as it has already been suggested in two previously published retrospective studies (17,35).…”
Section: Discussionmentioning
confidence: 99%
“…The onset of action can be expected after a few weeks. One study investigating tocilizumab treatment within 2 weeks after an NMOSD attack showed favorable effects on the disease course [ 63 ]. Nevertheless, data on the long-term use of tocilizumab in NMOSD remain scarce and mainly arise from other indications.…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%
“…Treatment for acute attacks consists of high-dose glucocorticosteroid (GC)-and apheresis therapy. The early initiation of B-cell and interleukin-(IL-6) directed therapies as add-on treatment to highdose steroid therapy during acute attacks improved outcomes in single case series but need to be evaluated in bigger studies [28,29]. The improved knowledge of the pathophysiology in NMOSD has led to the initiation of randomized and controlled trials with B-cell directed therapies, IL-6 directed therapy and anti-complement therapy.…”
Section: Therapeutic Approaches In Neuromyelitis Optica Spectrum Diso...mentioning
confidence: 99%